Preparation of hollow-fibre composite carbon-zeolite membranes - Smith, Sarel Petrus Jacobus (Stellenbosch : Stellenbosch University, 2012)
Dissertation (M. Sc. Polymer Science) -- University of Stellenbosch, 1995.